Systematic Review of the Relationship Between Handgrip Strength and Blood Glucose Levels in Young Adults and the Elderly - Lekan Sheriff Ojulari; Swabirah Eniamire Sulaiman; Olayide Sulaiman Agodirin; Mohammed Amali (Pan-African Journal of Health and Environmental Science)
Background: Handgrip strength (HGS) is an indicator of overall muscle health and is affected by impaired blood glucose levels. This review discusses the relationship between HGS and blood glucose levels and provides solutions to the known problems of HGS and blood glucose regulation.